Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.2 - More Work with Exponents and Scientific Notation - Exercise Set - Page 268: 38



Work Step by Step

$(\frac{7^{-3}}{ab^{2}})^{-2}$ Using $\frac{1}{a^{n}}= a^{-n}$ $= (7^{-3}a^{-1}b^{-2})^{-2}$ $= (7^{-3})^{-2}(a^{-1})^{-2}(b^{-2})^{-2}$ Using $(a^{m})^{n} =a^{m \times n} $ $=7^{6}a^{2}b^{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.